2009
DOI: 10.3748/wjg.15.5368
|View full text |Cite
|
Sign up to set email alerts
|

A latent form of essential thrombocythemia presenting asportal cavernoma

Abstract: Essential thrombocythemia is frequently associated with abdominal thrombotic complications including portal cavernoma as a consequence of chronic portal vein thrombosis. Essential thrombocythemia in a latent form is difficult to identify at onset due to the absence of an overt disease phenotype. In the presented case report, the diagnosis of essential thrombocythemia was initially missed because the typical disease phenotype was masked by bleeding and hypersplenism. The correct diagnosis was only reached when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…In non-cirrhotic and non-tumoral PVT cases in the West, MPD (i.e. polycythaemia vera, essential thrombocythaemia and myelofibrosis) with a combination of several prothrombotic factors constitute the most common identifiable cause with an estimated prevalence of 30%-60% (Cai et al, 2009;Kiladjian et al, 2006;Kutti & Ridell, 2001). In another study, a myeloproliferative disorder (MPD) was found in 37% of patients with non-cirrhotic non-malignant PVT (Kiladjian et al, 2006).…”
Section: Epidemiology Of Mpd With Pvtmentioning
confidence: 97%
See 2 more Smart Citations
“…In non-cirrhotic and non-tumoral PVT cases in the West, MPD (i.e. polycythaemia vera, essential thrombocythaemia and myelofibrosis) with a combination of several prothrombotic factors constitute the most common identifiable cause with an estimated prevalence of 30%-60% (Cai et al, 2009;Kiladjian et al, 2006;Kutti & Ridell, 2001). In another study, a myeloproliferative disorder (MPD) was found in 37% of patients with non-cirrhotic non-malignant PVT (Kiladjian et al, 2006).…”
Section: Epidemiology Of Mpd With Pvtmentioning
confidence: 97%
“…The annual incidence of myeloproliferative syndrome is 2,1-3,5 per 100000 peoples (Kutti & Ridell, 2001). From the four entities comprising the myeloproliferative syndrome according to the FAB classification (essential thrombocythemia, polycythaemia vera, chronic myelogenous leukemia and idiopathic myelofibrosis), essential thrombocythemia is considered the most frequent disease with an annual incidence of 0,7-2,5 per 100000 peoples (Cai et al, 2009;Girodon et al, 2009;Rollison et al, 2008). The transformation to acute myelogenous leukemia is recorded in 0,6-5% of patients and the overall 10-year survival rate is 64-80% (Fenaux et al, 1990).…”
Section: Epidemiology Of Mpd With Pvtmentioning
confidence: 99%
See 1 more Smart Citation
“…In non-cirrhotic and non-tumoral PVT cases in the West, MPD (i.e. polycythaemia vera, essential thrombocythaemia and myelofibrosis) with a combination of several prothrombotic factors constitute the most common identifiable cause with an estimated prevalence of 30%-60% (Cai et al, 2009;Kiladjian et al, 2006;Kutti & Ridell, 2001). In another study, a myeloproliferative disorder (MPD) was found in 37% of patients with non-cirrhotic non-malignant PVT (Kiladjian et al, 2006).…”
Section: Epidemiology Of Mpd With Pvtmentioning
confidence: 99%
“…From the four entities comprising the myeloproliferative syndrome according to the FAB classification (essential thrombocythemia, polycythaemia vera, chronic myelogenous leukemia and idiopathic myelofibrosis), essential thrombocythemia is considered the most frequent disease with an annual incidence of 0,7-2,5 per 100000 peoples (Cai et al, 2009;Girodon et al, 2009;Rollison et al, 2008). The transformation to acute myelogenous leukemia is recorded in 0,6-5% of patients and the overall 10-year survival rate is 64-80% (Fenaux et al, 1990).…”
Section: Epidemiology Of Mpd With Pvtmentioning
confidence: 99%